THE PROFILE OF DIGLOSSIC JAVANESE IN THREE GENERATIONS OF JAVANESE DESCENDANTS IN SITIUNG DHARMASRAYA - Melinda Pertiwi; Hamzah Hamzah; Leni Marlina (Universitas Negeri Padang, 2017)
Indonesian language consists of some different languages and dialects. This variety of language leads Indonesian people into bilingual, even multilingual community. The diglossic situation cannot be separated in daily life of people who lived in bilingual or multilingual society, such as Javanese language. The difference use of Krama (H variety), Madya (M variety) and Ngoko (L variety) obligated the speakers to know how to use the language function according to place and condition of the participants. This study investigates the profile of diglossic Javanese in three generations. This study aims to find out (1) the profile of diglossic Javanese, (2) the variety of language choice, and (3) the factor that affected the language choice. This research is a kind of descriptive research, because the researcher described and analyzed the profile of diglossic Javanese in three generation. The findings of this study reveal that in the first generation they are use H variety and M variety in communication, in the second generation they are use all of the three varieties depending whom they speak to. Meanwhile, in the third generations they mostly use ngoko (L variety). The used of krama lexicon was replacing with the lexicon of ngoko in third generation. There are several factors that have contributed to the respondents’ choice of using a certain variety when communicating. The used between the three varieties took place depending mostly on the addressee, the situation and the purposes of communication.